Substituting fossil-based with bio-based chemicals: the case of limonene as a greener pore expander for micellar templated silica - Sultan, Umair; Städtke, Katrin; Göpfert, Andreas; Lemmen, Daniel; Metwali, Ezzeldin; Maiti, Santanu; Schlumberger, Carola; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Vogel, Nicolas; Unruh, Tobias; et al. (RSC Sustainability, 2023)
Porous materials are widely used in applications such as adsorption, catalysis and separation. The use of expander molecules is a versatile route to enlarge the mesopore size in micellar templated mesoporous silica materials. Typical expanders used for this purpose are fossil-based organic molecules such as trimethylbenzene (TMB). In the course of making such syntheses greener and more sustainable, it is highly desirable to substitute such fossil-based chemicals with renewable ones. Here, we show that bio-based limonene can be used as an alternative expander molecule for the synthesis of large-pore templated silica. On the basis of electron microscopy, nitrogen physisorption and small angle X-ray scattering we show that the substitution of TMB by limonene leads to very similar material characteristics, reaching mean mesopore diameters of 17-19 nm. A comparative life-cycle assessment demonstrates the reduced environmental impact of limonene production from citrus peel waste compared to TMB production, supporting the call for more applications of renewable chemicals, ideally from waste-streams, also for the production of porous materials.
CRIS-Team Scopus Importer:2023-10-06

Towards a greener synthesis of dianhydrohexitol esters - Städtke, Katrin; Göpfert, Andreas; Inayat, Alexandra (Green Chemistry, 2023)
Esterification is an important reaction mechanism for the conversion of many bio-based molecules. In this work, we study the esterification of bio-based diols isosorbide and isomannide with different short-chain organic acids via two well-established esterification routes. Route 1 is Fischer esterification, i.e. it is catalytic and uses an organic acid as a reaction partner. Route 2 uses a more reactive acid anhydride instead of free acids, and therefore, it is faster and does not require a catalyst and entraining agent. A comparative cradle-to-gate life cycle assessment was conducted to identify the ecological advantages and disadvantages of each esterification route in order to conclude on their greenness and identify points for future improvement. It was found that Route 1 consumes around 30% less energy for the production of the reactants and auxiliaries compared to Route 2. However, Route 2 requires only 10% of the energy for the esterification process because of the much shorter reaction time (3 h) than that of Route 1 (30 h). Since the current global energy source mix is largely fossil-based, impacts related to emissions from energy production dominate the ecological impacts of both routes and scale with the total energy demand. Therefore, Route 2 is currently the greener one in most impact categories (global warming, fossil depletion and human toxicity potential) with the exception of a high water depletion potential (WDP), which is related to the acid anhydride production. If in future only renewable energy from sun, wind and water was used for ester production, both esterification routes would be much greener. With the current global energy mix, the greenness of Route 1 could be enhanced if the reaction time could be shortened, a well reusable catalyst could be found and if the recycling rate of the entrainer and excess acid could be further increased or their amount generally reduced.
CRIS-Team Scopus Importer:2023-09-08